Electrochemical Properties of Silver Nanoparticle Doped Aminosilica Nanocomposite. (6th September 2011) - Choi, Yong-Jae; Luo, Tzy-Jiun M.
Abstract : The electrochemical properties of silver nanoparticle ( d~ 5 nm) synthesized within aminosilica film from spontaneous reduction reaction were examined using cyclic voltammetry and the results show that the nanocomposite film exhibits similar redox property as solution-synthesized silver nanoparticles when measuring in phosphate buffer solution and its redox potentials were found to be sensitive to the presence of chloride ions. It also shows that silver nanoparticles and hydrolyzed aminosilica increase the electron diffusivity of the aminosilica film. Both results confirm that an accurate reference electrode suitable for microfluidic devices can be created simply by treating an aminosilica-coated electrode with a silver nitrate solution. Furthermore, a humidity sensor based on silver-silica nanocomposite film has also been demonstrated.